Factors Affecting Parental Anxiety Preschool After Treatment at the Indonesian Army Hospital TK IV IM 07.01 Lhokseumawe City - Rohana Rohana; Cut Linar; Wulandari Wulandari; Zulkifli Zulkifli (International Journal Of Health Science, 2025)
Anxiety is one of the common psychological responses experienced by parents when their children are hospitalized. This condition does not only last during hospitalization, but can also continue after the child is discharged, especially in preschool children who are still very emotionally dependent on their parents (Potts & Mandleco, 2012). The post-hospitalization period is a vulnerable time for parents because of concerns about the possibility of recurrence of the disease, complications, and limited knowledge in caring for children at home. This study aims to determine the Factors that Influence the Anxiety of Parents of Preschool Children After Hospitalization. This study used a quantitative approach with a cross-sectional study method. The results showed that most respondents were in the young adult category as many as 53 people (45.7%), respondents had incomes in the middle category as many as 54 people (46.6%), respondents with health factors were in the low category as many as 62 people (53.4%). Health factors in this context include knowledge, awareness, and behavior of parents towards promotive and preventive efforts in maintaining children's health before and after hospitalization. It is recommended that hospitals provide home visits or follow-up services via telephone/teleconsultation to monitor the child's condition while providing psychosocial support for parents